Discovery of prostate specific antigen pattern to predict castration resistant prostate cancer of androgen deprivation therapy. - Yejin Kim; Park, Yong Hyun; Ji Youl Lee; In Young Choi; Hwanjo Yu; Kim, Yejin; Lee, Ji Youl; Choi, In Young; Yu, Hwanjo (BMC Medical Informatics & Decision Making, 2016)
Background: Prostate specific antigen (PSA) is an important biomarker to monitor the response to the treatment, but has not been fully utilized as a whole sequence. We used a longitudinal biomarker PSA to discover a new prognostic pattern that predicts castration-resistant prostate cancer (CRPC) after androgen deprivation therapy.Methods: We transformed the longitudinal PSA into a discrete sequence, used frequent sequential pattern mining to find candidate patterns from the sequences, and selected the most predictive and informative pattern among the candidates.Results: Patients were less likely to be CRPC if, after PSA values reach nadir, the PSA decreases more than 0.048 ng/ml during a month, and the decrease occurs again. This pattern significantly increased the accuracy of predicting CRPC by supplementing information provided by existing PSA patterns such as pretreatment PSA.Conclusions: This result can help clinicians to stratify men by the risk of CRPC and to determine the patient that needs intensive follow-up.